Influence of the Structural Period in the Input Energy Power - Frau, Carlos; Panella, Sebastián; Gioacchini, Gustavo (Universidad Tecnológica Nacional. Faculatd Regional Mendoza, 2025)
Performance-Based Seismic Engineering requires the evaluation of AQ1 ground motion intensity measures. This is also necessary for Energy-Based Design methodology which effect of ground motions on structures is considered as an energy input to structures. It is known that intensity measures of ground motion based on energy allow an improved characterization of different types of time histories. This is because energy is a cumulative measure of ground shaking and it captures the duration effects, frequency content and amplitude. In particular, the time that the ground motions deliver the energy is a relevant aspect that differs from the traditional acceleration response spectra which represents only the maximum response. To take in count the time in which the energy enters in the structure, and should be dissipated, previous works have introduced the power concept; it is defined as the total input energy divided by the time energy takes to enter to the structure. In the definition of the time to calculate the power the effective duration of the acceleration time history was used as the time interval between the 5% and 95% of the Arias Intensity. In this work the time interval in which the energy enter to the structure is studied. The time to calculate the power is obtained from the graph of input energy for each structural period. Thus, the parameters named as Input Energy Power, Input Energy Power Spectrum and Input Energy Power Intensity are redefined from this new definition of time. It was found that the time which the energy enters to the structure changes significative from a period to another, especially in near-fault record. When this time is compared with the structural period it is observed that in some cases the structures should dissipate a great amount of energy in a few strain cycles.
Keywords: Energy-Based Design; Input Energy Power; Influence of the structural period